Emphasis in Arabic is a study in the light of implicit patterns: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - .lateef abdulsada sarhan , Professor Dr (lark, 2022)
The large number of emphases in Arabic and the multiplicity of its patterns and the diversity of its methods represent a linguistic phenomenon with an influential semantic value, for its control in determining the meanings and revealing the intentions in the discourse. The emphatic in his communicative discourse as well as its linguistic motives and linguistic extensions; The implicit patterns that are embedded in the emphasis structure constitute a dangerous epistemological mulch in its formation and its frequent circulation stemming from the conflict of the Bedouin and urban environments, and the communicative gap and discontinuity caused by that conflict in the discourse chain, so the affirmation comes with its abundant credentials to bridge the crack of that chain and restore its reporting communication in the receiving space.